Why is adaptive policy important in geosite governance as an effort to realize sustainable tourism in the Toba Caldera Geopark area of Samosir regency? - Hajar, Siti; Ramlan; Kholik, Kholilul (Frontiers in Political Science, 2025)
Geosites as geopark assets not only have ecological and geological value, but also socio-cultural and sustainable economic value for local communities. The purpose of this study is to analyze the importance of adaptive policies in geosite governance by considering environmental dynamics, community involvement, and global challenges including climate change and sustainable tourism. The research method used a mixed methods approach with a sequential explanatory design. Quantitative data were obtained through a survey of stakeholders involved in geosite management, then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine factors influencing the effectiveness of adaptive policies. Furthermore, qualitative analysis was carried out to strengthen the quantitative results and provide contextual understanding. The results show that adaptive policies have a significant role in increasing the effectiveness of geosite governance in realizing sustainable tourism through existing local values. Then, the main contributing factors are cross-sector collaboration, recognition of local wisdom, and policy flexibility in responding to changing socio-economic and environmental conditions. Thus, adaptive policies are seen as an important foundation in realizing the sustainability of the Toba Caldera Geopark and supporting the achievement of the Sustainable Development Goals (SDGs).